How does the collaborative innovation network in construction industry evolve? Evidence from China - Wang, Fangliang; Cheng, Min (Journal of Civil Engineering and Management, 2025)
Technology innovation in the construction industry involves collaboration among multiple innovation organizations which formed an intricate collaborative innovation network (CIN). To understand the evolution characteristics of structural characteristics of CIN in China’s construction industry and to clarify the collaborative patterns among innovation organizations, the CIN were analyzed in terms of overall network characteristics and local collaborative patterns by using the social network analysis (SNA) and network motif analysis (NMA), respectively based on the data of projects winning the China’s Science and Technology Award in Construction (CSTAC) in 2004–2021. The results indicate that the CIN became larger but less connected and exhibited scale-free and small-world characteristics during the study period. There is a giant component in the CIN, which is gradually increasing in size and becoming more cohesive. China Academy of Building Research which had the highest degree centrality and closeness centrality and Tongji University which had the largest betweenness centrality had an important position in CIN. The main collaborative innovation mode in China’s construction industry is collaboration between enterprises, followed by collaboration between enterprise-university, which has an increasing share. The results help organizations clarify their position in the CIN and inform their development of co-innovation partners.